Photoluminescence of boron nitride nanosheets exfoliated by ball milling - Hua Li, Lu; Chen, Ying; Cheng, Bing-Ming; Lin, Meng-Yeh; Chou, Sheng-Long; Peng, Yu-Chain (Applied physics letters, 2012)
The photoluminescence of boron nitride (BN) nanosheets exfoliated by ball milling method has been investigated. At room temperature, the nanosheets have strong deep ultraviolet (DUV) light emission at 224 nm and weak defect-related UV (∼300 nm) emission. The DUV peak profile slightly changes with the increase of milling time due to the increase of stacking faults caused by the shear force during milling. The decreased ∼300 nm emission after milling treatments has been attributed to the preferential orientation of the BN nanosheets on substrate and the strong polarization anisotropy of BN materials in luminescence.